The status of the canonical form of marriage in Papua New Guinea: A comparative study of customary, statutory and canonical celebration of marriage. - Dikos, Peter. (University of Ottawa (Canada), 2005)
The people in Papua New Guinea contract marriage according to their traditional, customary law, normally in every case prior to any Christian rite of marriage. From the time of their customary marriage, even Catholics, consider themselves properly married. Nevertheless, they are aware that they cannot receive the Eucharist as long as they remain unmarried in the eyes of the Church. If it takes place at all, the Church marriage is often celebrated years after the customary marriage and this rite loses its meaning for the couple and many Catholics think that a Church marriage contributes, if anything, little to the married state. At best it regularizes a couple's position before the priest and this provides access to the Eucharist. This attitude and the low percentage of Catholics who celebrate their marriage in the canonical form has been a matter of increasing concern to the Church in Papua New Guinea. Customary marriage differs from the Western form of marriage in two respects: (a) It comes into being in the course of protracted negotiations between the families of the bridegroom and the bride. Various stages in the negotiations are marked by various ceremonies; (b) while free choice and consent of the parties is in no way precluded, the inter-familial relationship is an inseparable characteristic of the marriage according to Papua New Guinean customs. It was with an intention of identifying and proposing an equitable solution the pastoral problems related to marriage and family life in Papua New Guinea that we undertook our study regarding the status of the canonical form of marriage in Papua New Guinea. The status quaestionis of study was: How might the customary laws expressed in the traditional celebration of marriage be safeguarded and yet contextualized within the Church's legislation on the canonical form of marriage? This status quaestionis is answered in four inter-related chapters. The principal conclusion of our study suggests that the most serious feature of a low marriage rate in the church is the separation in time of the customary and sacramental marriage, which leads to a widespread view that sacramental marriage is largely irrelevant. For this reason, we discuss at length in the fourth chapter the compatibility between the notions of a natural contract (contractum naturale) and the sacramental marriage. The integration of the customary celebration, that is, natural marriage, and the canonical celebration is possible only when marriage is actually celebrated within a cultural context that conforms to the customary legal traditions of people. Because of this compatibility between the two forms of marriage, any adaptation of the canonical form of marriage to customary celebration must take into consideration the different roles the lay people, that is, the leaders of the communities or elders of families as well as the priest have to play. (Abstract shortened by UMI.)
Keywords: Religion, General.; Law.